Ribosome quality control is a central protection mechanism for yeast exposed to deoxynivalenol and trichothecin. (December 2016) - Kugler, Karl; Jandric, Zeljkica; Beyer, Reinhard; Klopf, Eva; Glaser, Walter; Lemmens, Marc; Shams, Mehrdad; Mayer, Klaus; Adam, Gerhard; Schüller, Christoph
Abstract Background The trichothecene mycotoxins deoxynivalenol (DON) and trichothecin (TTC) are inhibitors of eukaryotic protein synthesis. Their effect on cellular homeostasis is poorly understood. We report a systematic functional investigation of the effect of DON and TTC on the yeastSaccharomyces cerevisiae using genetic array, network and microarray analysis. To focus the genetic analysis on intracellular consequences of toxin action we eliminated thePDR5 gene coding for a potent pleiotropic drug efflux protein potentially confounding results. We therefore used a knockout library with apdr5 Δ strain background. Results DON or TTC treatment creates a fitness bottleneck connected to ribosome efficiency. Genes isolated by systematic genetic array analysis as contributing to toxin resistance function in ribosome quality control, translation fidelity, and in transcription. Mutants in the E3 ligase Hel2, involved in ribosome quality control, and several members of the Rpd3 histone deacetylase complex were highly sensitive to DON. DON and TTC have similar genetic profiles despite their different toxic potency. Network analysis shows a coherent and tight network of genetic interactions among the DON and TTC resistance conferring gene products. The networks exhibited topological properties commonly associated with efficient processing of information. Many sensitive mutants have a "slow growth" gene expression signature. DON-exposed yeast cells increase transcripts of ribosomal protein and histone genes indicating an internal signal for growth enhancement. Conclusions The combination of gene expression profiling and analysis of mutants reveals cellular pathways which become bottlenecks under DON and TTC stress. These are generally directly or indirectly connected to ribosome biosynthesis such as the general secretory pathway, cytoskeleton, cell cycle delay, ribosome synthesis and translation quality control. Gene expression profiling points to an increased demand of ribosomal components and does not reveal activation of stress pathways. Our analysis highlights ribosome quality control and a contribution of a histone deacetylase complex as main sources of resistance against DON and TTC.